Marketing Issues Faced by Potato Growers and Intermediaries in Parwan, Afghanistan - Lalzai, Faridullah; Jamali, Akhtar Jamal; Naziri, Abdul Mutaleb; Jamali, Nik Jamal (Journal for Research in Applied Sciences and Biotechnology, 2023)
This research paper investigated the marketing challenges faced by potatoes growers and market intermediaries in Parwan province, Afghanistan. The study analysed the field level problems of farmers, consumers, wholesalers, and retailers. The study revealed that farmers encounter various obstacles in potato marketing, with the far-off location of selling markets 40.80 percent , lack of grading facilities 35.80 percent , and transportation issues 35.00 percent strongly agree, and that were being prominent concerns. Additionally, market information gaps 26.70 percent and malpractices by buyers 30.80 percent impact the marketing process. The study also examined consumers' difficulties in purchasing potatoes, indicating issues with timely product availability 18.80 percent strongly agree. Price fluctuations 37.50 percent strongly agree, and inadequate packaging 18.80 percent strongly agreed. Furthermore, consumers expressed concern about potato grading 37.50 percent agreed and quality 37.50 percent strongly agree. Another aspect of the study investigated wholesalers' challenges, identifying the absence of grading facilities 80.00 percent strongly agree. Storage 80.00 percent strongly agreed, and transportation issues 60.00 percent strongly agreed, as key constraints. Wide price fluctuations 70.00 percent strongly agreed, and inaccurate weighing 80.00 percent. Lastly, the research explored retailers' obstacles in potato marketing, highlighted issues with grading facilities 90.00 percent strongly agreed, storage 80.00 percent strongly agreed, and transportation 70.00 percent strongly agreed. Additionally, retailers face challenges with price fluctuations 80.00 percent strongly agree, and selling lower-grade potatoes 70.00 percent strongly agree.